Parasite clearance dynamics in children hospitalised with severe malaria in the Ho Teaching Hospital, Volta Region, Ghana - Laura Paris; Richmond G. Tackie; Khalid B. Beshir; John Tampuori; Gordon A. Awandare; Fred N. Binka; Britta C. Urban; Bismarck Dinko; Colin J. Sutherland (Parasite Epidemiology and Control, 2022)
Background: Over 90% of severe malaria (SM) cases occur in African children. Parenteral artesunate is currently the recommended treatment for SM. Studies of parasite clearance in paediatric SM cases are needed for assessment of therapeutic outcomes but are lacking in Africa. Methods: Severe malaria patients were recruited in the children's emergency ward at Ho Teaching Hospital, Ghana, in 2018. Blood samples were taken upon admission, every 24 h for 3 days and 1 week after treatment, and DNA extracted. Parasitaemia and parasite densities were performed by microscopy at enrolment and the follow-up days wherever possible. Relative parasite density was measured at each timepoint by duplex qPCR and parameters of parasite clearance estimated. Results: Of 25 evaluable SM patients, clearance of qPCR-detectable parasites occurred within 48 h for 17 patients, but three out of the remaining eight were still qPCR-positive on day 3. Increased time to parasite clearance was seen in children ≥5 years old, those with lower haemoglobin levels and those with a high number of previous malaria diagnoses, but these associations were not statistically significant. Conclusion: We examined parasite clearance dynamics among paediatric cases of SM. Our observations suggest that daily sampling for qPCR estimation of P. falciparum peripheral density is a useful method for assessing treatment response in hospitalised SM cases. The study demonstrated varied parasite clearance response, thus illuminating the complex nature of the mechanism in this important patient group, and further investigations utilizing larger sample sizes are needed to confirm our findings.